A New Method for Improving Extraction Efficiency and Purity of Urine and Plasma Cell-Free DNA - Lin, Selena Y. (Diagnostics (Basel), 2021)
This study assessed three commercially available cell-free DNA (cfDNA) extraction kits and the impact of a PEG-based DNA cleanup procedure (DNApure) on cfDNA quality and yield. Six normal donor urine and plasma samples and specimens from four pregnant (PG) women carrying male fetuses underwent extractions with the JBS cfDNA extraction kit (kit J), MagMAX Cell-Free DNA Extraction kit (kit M), and QIAamp Circulating Nucleic Acid Kit (kit Q). Recovery of a PCR product spike-in, endogenous TP53, and Y-chromosome DNA was used to assess kit performance. Nucleosomal-sized DNA profiles varied among the kits, with prominent multi-nucleosomal-sized peaks present in urine and plasma DNA isolated by kits J and M only. Kit J recovered significantly more spike-in DNA than did kits M or Q (p < 0.001) from urine, and similar amounts from plasma (p = 0.12). Applying DNApure to kit M- and Q-isolated DNA significantly improved the amplification efficiency of spike-in DNA from urine (p < 0.001) and plasma (p ≤ 0.013). Furthermore, kit J isolated significantly more Y-chromosome DNA from PG urine compared to kit Q (p = 0.05). We demonstrate that DNApure can provide an efficient means of improving the yield and purity of cfDNA and minimize the effects of pre-analytical biospecimen variability on liquid biopsy assay performance.